Rewriting the Jew : Assimilation Narratives in the Russian Empire. - Safran, Gabriella (Contraversions (Stanford, Calif.), 2000)
"In the Russian Empire of the 1870s and 1880s, while intellectuals and politicians furiously debated the "Jewish Question," more and more acculturating Jews, who dressed, spoke, and behaved like non-Jews, appeared in real life and in literature. This book examines stories about Jewish assimilation by four authors: Grigory Bogrov, a Russian Jew; Eliza Orzeszkowa, a Polish Catholic; and Nikolai Leskov and Anton Chekhov, both Eastern Orthodox Russians. Safran introduces the English language reader to works that were much discussed in their own time, and she situates Jewish and non-Jewish writers together in the context they shared."